Machine Vision Automated Visual Inspection: Theory, Practice and Applications - Beyerer, Jürgen; Puente León, Fernando; Frese, Christian (Springer Berlin Heidelberg : Imprint: Springer, 2016)
The book offers a thorough introduction to machine vision. It is organized in two parts. The first part covers the image acquisition, which is the crucial component of most automated visual inspection systems. All important methods are described in great detail and are presented with a reasoned structure. The second part deals with the modeling and processing of image signals and pays particular regard to methods, which are relevant for automated visual inspection.